Erratum: Measurement of the D*(2010)+ natural linewidth and the D*(2010)+-D0 mass difference - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
[Phys. Rev. D 88, 052003 (2013)] DOI:https://doi.org/10.1103/PhysRevD.88.079902